PHYLOGENETIC ANALYSIS OF AQUILARIA AND GYRINOPS MEMBER BASED ON TRNL-TRNF GENE SEQUENCE OF CHLOROPLAST - I Gde Adi Suryawan Wangiyana (JURNAL SANGKAREANG MATARAM, 2016)
Aquilaria and Gyrinops are main agarwood producers that only could be distinguished based on their flower structure. Molecular characteristic analysis is needed to support morphological character for breeding and conservation purpose. Several molecular analyses were conducted based on similarity characteristic of Aquilaria and Gyrinops. However phylogenetic analysis of these genera was so few to support the polyphasic classification. The purpose of this study is to do phylogenetic analysis based on trnL-trnF sequence. Thirteen sequences of Aquilaria and six sequences of Gyrinops were downloaded from NCBI. ClustalX 2.1 program were used for multiple alignment of sequences. Three phylogenetic trees were reconstructed with MEGA 5.1 by different method including: Neighbor Joining, Minimum and Maximum Liklihood. Phydit program were used to construct similarity matrix between sequences. Based on phylogenetic analysis, all Aquilaria members were clustered in the same clade. All sister taxa also composed with Aquilaria member except for A.hirta. On the other hand, G.salicifora, G.Podocarpa and G.Ladermanii are the only Gyrinops members that form same clade. Other Gyrniops members were spread to different clade. It could be concluded that trnL-trnF sequence is a useful phylogenetic marker for Aquilaria although have several limited for Gyrinops. Moreover, based on phylogenetic analysis and similarity analysis it could be suggested that Aquilaria and Gyrinops sould not be separated into different genera.